Chemical metabolic behaviour of the soleus muscle during the acute phase of joint immobilisation (Fisioterapia e Pesquisa, 2008)
The purpose of this study was to outline a physiological profile of the soleus muscle during the acute phase of joint immobilization at a 90º position. Male Wistar rats were divided into four groups (n=6): Control (C), immobilised for 1 (Im1), 2 (Im2), and 3 (Im3) days. After the experimental period, the soleus muscle was obtained in order to assess: glycogen content, muscle weight, hydration index, and protein-DNA interactions. Data were statistically analysed and significance level set at p